Influence of serum vitamin D levels on control and severity of asthma in children - R., Savitha M.; Pawar, Gayatri R. (International Journal of Contemporary Pediatrics, 2020)
Background: To determine the association between the serum vitamin D levels with the control and severity of asthma. Methods: A total of 113 asthmatic children were enrolled in the study who were on regular follow-up and treatment for the past 6 or more months. The demographic details, presenting complaints, aggravating factors, allergic rhinitis, atopic dermatitis, hospital and ICU stay, duration of sunlight exposure, drug compliance and detailed clinical examination findings were noted in the predesigned proforma. Control of asthma was assessed based on GINA guidelines 2018 as well controlled, partly controlled and poorly controlled. The partly controlled and the poorly controlled group were further combined and labelled as not well controlled group. Severity of asthma was categorized into intermittent, mild persistent, moderate persistent and severe persistent. Serum 25 hydroxy vitamin D was assessed by solid phase ELISA. The well controlled and partly controlled group were compared for all studied parameters. Results: Asthma status of the subjects was categorized as well controlled (59%) as partly controlled (40%) and as poorly controlled (1%). Children with partly and poorly controlled asthma had significantly more vitamin D deficiency (10.9%) and insufficiency (32.6%) compared to well controlled group (4.5% and 4.5% respectively), with p value= 0.000. Low serum vitamin D levels are significantly associated with moderate and severe persistent asthma (p value= 0.009). Exercise significantly induced symptoms in 47.8% of not well controlled group and about 25.4% in well controlled group (p value= 0.014). Examination findings such as wheeze on auscultation was significantly more in not well controlled group. Conclusions: Low serum vitamin D levels are associated with poor control of asthma in children and the severity of asthma is inversely proportional to the serum vitamin D levels.